2017
DOI: 10.15261/serdj.24.71
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Equilibria for the Solvent Extraction of Ammonia with LIX84I

Abstract: Solvent extraction of valuable metals such as copper and nickel is often carried out from ammoniacal alkaline solutions with chelating extractants, during which coextraction of ammonia is inevitable. In the present study, as a basis of modeling of the whole ammoniacal extraction process, the equilibrium distribution ratios of ammonia between a 3 mol L -1 ammonium nitrate solution and LIX84I (the active component of which is 2-hydroxy-5-nonylacetophenone oxime, HR) dissolved in a nonpolar diluent were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…In our previous paper 19) , we examined the equilibria established during the extraction of ammonia with LIX84I (active component, 2-hydroxy-5-nonylacetophenone oxime, HR) from a 3 kmol m −3 solution of ammonium nitrate in the absence of metal ions, and found that the distribution ratios obtained experimentally were in good agreement with those calculated by an equilibrium model which assumed the formation of adducts between ammonia and the extractant.…”
Section: Introductionmentioning
confidence: 73%
“…In our previous paper 19) , we examined the equilibria established during the extraction of ammonia with LIX84I (active component, 2-hydroxy-5-nonylacetophenone oxime, HR) from a 3 kmol m −3 solution of ammonium nitrate in the absence of metal ions, and found that the distribution ratios obtained experimentally were in good agreement with those calculated by an equilibrium model which assumed the formation of adducts between ammonia and the extractant.…”
Section: Introductionmentioning
confidence: 73%
“…19) The concentration of ammonia in the loaded organic phase was determined in the same way after complete stripping with 0.1 kmol m ¹3 HCl. 17) Distribution ratios of the metals ion M 2+ (where M = Ni or Cu) (D(M)) and of NH 3 (D(NH 3 )) were calculated as…”
Section: Extraction Of Nickel Copper and Ammoniamentioning
confidence: 99%
“…Here i denotes the order of aggregation and a positive integer ranging to infinity, and K m is assumed to be independent of i. 17) nickel, and copper 18) Extraction equilibrium of ammonia with HR (K 1 ) is expressed as…”
Section: Equilibria In the Aqueous Phasementioning
confidence: 99%
See 2 more Smart Citations